Jaguars and raptorial birds: the ancient wood carving arts of Northeastern South America (Trombetas River region, Brazil) - Ostapkowicz, Joanna; Widenhoeft, Alex C.; Brock, Fiona; Snoeck, Christophe; Cartwright, Caroline; Uden, Jeremy; Baittinger, Claudia; Gabriel, Mille; Gordon, Julie; Richardin, Pascale; Lavier, Catherine; Clauzel, Thibault; et al. (Elsevier, 2026)
This paper presents the results of the first systematic study aimed at defining the chronology, provenience and material components of 14 distinctive wood carvings featuring jaguar and raptorial bird imagery broadly attributed to northeastern South America, centred on Brazil’s Trombetas River region. These carvings, largely confined to drug-related paraphernalia and ceremonial objects (trumpets, rattles, staffs/sceptres and a hafted anchor axe), were part of antiquarian collections deposited in European museums mainly in the 19th century, with very little associated information.14C AMS dating of their wood, cotton and resins shows that they have deeper histories, spanning the 14th to late 17th/early 18th centuries. Wood identification indicates a relatively narrow range of taxa, mainly from the genera Brosimum and Swartzia, likely selected for their hardness and striking “snakeskin” or “leopard skin” patterns. Bindings of human hair are identified on a ceremonial weapon. Strontium isotope (87Sr/86Sr) analysis of the wood is used to explore the possible provenience of the carvings, with the results divided into two groups, one from a more radiogenic region consistent with the Trombetas, and the other from a less radiogenic region, possibly the Amazon floodplain.
Keywords: 4301 Archaeology; 4303 Historical Studies; 43 History, Heritage and Archaeology; Pre-Colonial/early Colonial Brazil; Jaguar imagery; Wood carving; Trombetas River; Museum collections; Radiocarbon dating; Strontium isotopes